Exploring Brand Loyalty: Revealing the Effect of Brand Experience Mediated by Brand Love and Trust among Smartphone Users in Malang City - Firdausiah, Rr Ayu; Sunaryo, Sunaryo; Sumiati, Sumiati; Abidin, Nurul Aini Binti Zainal (Universitas Brawijaya, Indonesia, 2024)
Increasingly fierce competition in the smartphone industry encourages companies to design mature marketing strategies to create added value for consumers and build strong relationships with their consumers. This study aims to identify and analyze the direct and indirect effects of brand experience, brand love, brand trust, and brand loyalty on Samsung smartphone users in Malang City. Data for this was collected through a questionnaire and a sample of 140 smartphone users in Malang City. Sample selection was carried out using the purposive random sampling method. The collected data will be analyzed using SmartPLS 3.0. These results reveal that brand experience has no direct effect on brand loyalty. However, this study confirms an indirect influence of brand experience on brand loyalty through brand love and trust. The results have important implications for building strong emotional relationships and bonds between brands and consumers, and it is necessary to use cognitive and affection factors to create brand loyalty.